1992
DOI: 10.1152/jappl.1992.73.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lung volume and alveolar pressure on reverse pulmonary venous blood flow

Abstract: We have reported that left atrial blood refluxes through the pulmonary veins to gas-exchanging tissue after pulmonary artery ligation. This reverse pulmonary venous flow (Qrpv) was observed only when lung volume was changed by ventilation. This was believed to drive Qrpv by alternately distending and compressing the alveolar and extra-alveolar vessels. Because lung and pulmonary vascular compliances change with lung volume, we studied the effect of positive end-expiratory pressure (PEEP) on the magnitude of Qr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The effect of ventilation on the movement of pulmonary vascular blood and the potential delivery of nutrients during ischemia depends on the type of ventilation, the vascular pressure, and the patency of the pulmonary artery and vein (32). For example, Obermiller et al (32) showed that positive-pressure ventilation caused reverse pulmonary venous blood flow in an in situ ischemic dog lung with patent pulmonary veins by cyclic ventilatory compression of alveolar capillaries. We reasoned that ventilating by lowering the surface pressure of the lung and keeping alveolar pressure constant relative to vascular pressure would minimize this effect, because the tidal emptying and filling of the alveolar vessels would be eliminated (39).…”
Section: Ventilation In Ischemic Lung Injurymentioning
confidence: 99%
“…The effect of ventilation on the movement of pulmonary vascular blood and the potential delivery of nutrients during ischemia depends on the type of ventilation, the vascular pressure, and the patency of the pulmonary artery and vein (32). For example, Obermiller et al (32) showed that positive-pressure ventilation caused reverse pulmonary venous blood flow in an in situ ischemic dog lung with patent pulmonary veins by cyclic ventilatory compression of alveolar capillaries. We reasoned that ventilating by lowering the surface pressure of the lung and keeping alveolar pressure constant relative to vascular pressure would minimize this effect, because the tidal emptying and filling of the alveolar vessels would be eliminated (39).…”
Section: Ventilation In Ischemic Lung Injurymentioning
confidence: 99%
“…The lung apparently also can receive significant oxygenation through reverse perfusion through the pulmonary veins after pulmonary artery occlusion when the lung is ventilated. This provides distending mechanical forces on the veins to move blood into the alveolar capillaries from the left atrium (339,340). Hamvas et al (28) found that transcapillary albumin flux was only increased in static lungs inflated with oxygen but not in lungs ventilated with either oxygen, pure nitrogen, or a nitrogen -5% CO 2 mixture.…”
Section: Ischemia-reperfusion Lung Injurymentioning
confidence: 99%
“…A potential problem with interpretation of our data is the presence of a reflux flow from the pulmonary venous circulation (4). This reflux flow may contribute a small amount of inert gas to the alveolar vessels in an amount dependent on ventilation (8,9). We studied two additional animals to determine the contribution of alveolar exchange in the left lung both before and after left pulmonary artery occlusion, using MIGET.…”
Section: Summary Of Findingsmentioning
confidence: 99%